Model keputusan investasi pengembangan perikanan tangkap rajungan di Desa Bungin Permai Kecamatan Tinanggea - Astuti, Sri Rahayu; Mansyur, Akhmad; Abdullah; Lawelle, Sjamsu Alam; Sidiq, Azwar (Universitas Halu Oleo, 2024)
This research aims to: (1) determine the feasibility of the crab fishing business in Bungin Permai Village, (2) to determine the sensitivity of the financial analysis model for crab fishing businesses based on changes in selling prices due to inflation. The research was conducted in July 2023. This research used the slovin technique with a total of 10 fishermen as respondents. Data collection was carried out using observation, interviews, documentation and literature review techniques. The types of data used were primary data and secondary data. The data analysis used was NVP, IRR, RCR, and sensitivity analysis. The research results showed that (1) the crab fishing business in Bungin Permai Village could be developed and it was feasible to continue because of the results of the feasibility analysis the business NPV value was IDR 83,363,842 (>0), the IRR was 74%, and the profit from the RCR was 52% . (2) based on the results of the sensitivity analysis model test with the scenario of an increase in the price of crab material, it was said that it was still feasible when the increase is 3.61% and 1.62%, whereas when the price of crab material increases by 50%, the business was not worth continuing and the selling price decreases. Crab crabs are said to still be viable when the selling price of crabs falls and price inflation remains at 3.61% and 1.62%, whereas when the selling price decreases by 35% the business was no longer worth continuing or continuing.